ANALYSIS OF THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE (GCG) PRINCIPLES AND TRIPLE BOTTOM LINE PRINCIPLES IN CORPORATE SOCIAL RESPONSIBILITY (CSR) PROGRAMS IN PT. XYZ - Felisha Adiva; Maria Theresia Heni Widyarti; Arum Febriyanti Ciptaningtias (Applied Accounting and Management Review (AAMAR), 2023)
The company's business activities will become more efficient if the company can apply the principles of Good Corporate Governance (GCG) with full commitment, including in implementing Corporate Social Responsibility (CSR) programs. In addition to the GCG principles, the implementation of CSR programs also needs to pay attention to the Triple Bottom Line principles to have a valuable impact on the sustainability of the company. This research is descriptive-quantitative research that aims to analyze the implementation of CSR programs and analyze the application of GCG and Triple Bottom Line principles in the CSR program of PT XYZ. Data collection was conducted through interviews, questionnaires, and documentation. Respondents related to the distribution of questionnaires are the recipients of the Community Development Program Year 2022-2023. The data analysis used is descriptive analysis to get the index value. The results showed that GCG principles and Triple Bottom Line principles have been applied to the CSR program of PT XYZ. However, the implementation of GCG principles related to the principles of transparency and responsibility as well as the implementation of Triple Bottom Line principles related to people still have shortcomings.